A,The Analysis of the Negative Impact of Marketplace on Facebook: User Security and Privacy Perspectives - anita azmi tarigan anita; Alya Sabrina alya; Tria pasya tria (Yayasan Sinergi Multidimensi Kreatif, 2024)
In today's digital era, online marketplaces such as those on the Facebook platform have experienced rapid growth. However, this growth has also caused various negative impacts, especially in terms of user security and privacy. This research aims to analyze thse negative impacts caused by the Facebook marketplace from the perspective of user security and privacy, using a Big Data-based approach. The research methods used include analysis of transaction data, user interaction patterns, as well as leakage of personal information that can be exploited unlawfully. The findings of this study highlight the challenges faced by users in maintaining their privacy in a marketplace environment full of big data. The implication of this research is the need for stricter policies and effective control mechanisms to protect user security and privacy in today's digital context. Keyword : Analytics, User security, User privacy, Big data, Perspective